Taksiran Kerugian Ekonomi Penyakit Kluron Menular (Brucellosis) pada Populasi Ternak di Indonesia (THE ESTIMATION OF ECONOMIC LOSSES CAUSED BY BRUCELLOSIS IN LIVESTOCK POPULATION IN INDONESIA) - Basri, Chaerul; Sumiarto, Bambang (Jurnal Veteriner; Vol 18 No 4 (2017), 2018)
Brucellosis is one of the constraints in development of animal husbandry in Indonesia and is thought to have a huge economic impact. This study aimed to calculate the national economic losses cause by brucellosis in livestock in Indonesia. The method of calculating the estimated economic losses used two ways, by calculating the direct losses and by calculating the price of economic externalities. Source of secondary data for the calculation derived from scientific publications, government data, expert opinions, market data, and assumptions that are based on expert discussions. The results showed that by the direct calculation method it is estimated the economic losses at approximately Rp. 3,516,401,986,082 per year whilst by the second method the losses is estimated at Rp. 3,637,773,925,000 per year. Both methods of calculation used give relative similar economic losses estimation. The total loss due to brucellosis is estimated to reach 1.8% of the total value of livestock assets in Indonesia.